“Influencia del nitroplus 9 combinado con stimulate en la emisión de brotes y formación de hojas de vid (borgoña negra) San Antonio de Cumbaza-San Martín” - Águila García, Eduardo Del (2003)
The present work has as title "it lnfluences of the Nitroplus 9 cocktail with Stimulate in the emission of buds and formation of vine leaves (black Burgundy) in San Antonio of Cumbaza - San Martin".; likewise with the objective to Evaluate the effect of different dose of the Nitroplus 9 cocktail with Stimulate in the uniformity of buds and formation of leaves, applying after the pruning in Vine variety Black Burgundy (lsabella) in San Antonio of Cumbaza; among Julio's months - November of the 2000 and to determine the economic analysis of the treatments in study; he/she was carried out in the District of San Antonio of Cumbaza, the gentleman's Key land San Martin Pineda, located in the sector "The Hill"; the area presents a fairly humid and warm climate. An annual half precipitation of 1400 - 2000 mm/año. half Temperature of 23.95 ºC, maxim of 27.50 ºC and mínimum of 20.40 ºC;. likewise a Relative Humidity of 81.75 to 84.25%. The used design was at random of Complete Blocks (DBCA), with 5 treatment with four repetitions. The treatments were T1 (Nitroplus 1 O+ 0.5 Stimulate), T2 (15 Nitroplus + 0.5 Stimulate), T3 (20 Nitroplus + 0.5 Stimulate), T4 (25 Nitroplus + 0.5 Stimulate), T5 (00 Nitroplus + 00 Stimulate). The results demonstrated that the biggest yields were obtained in the treatment 4(25 Nitroplus + 0.5 Stimulate 1) with 6 850.00kilos, with a net utility of 6 " 080.15nuevos suns and that of smaller yield was the treatment 5 (00 Nitroplus + 00 Stimulate) with 1 5 450.50kilos with a net utility of 4 809.28nuevos suns.